Association of Ontario’s Ban on Menthol Cigarettes With Smoking Behavior 1 Month After Implementation - Chaiton, Michael (JAMA Intern Med, 2018)
This study compares respondents’ planned behavior before the 2017 menthol cigarette ban in Ontario with actual behavior 1 month after the ban.